2001
DOI: 10.1002/1522-2683(200108)22:13<2631::aid-elps2631>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

An exactly solvable Ogston model of gel electrophoresis: VIII. Nonconducting gel fibers, curved field lines, and the Nernst-Einstein relation

Abstract: In this article, we examine the low-field electrophoretic migration of infinitely small analytes in dilute sieving media made of nonconducting gel fibers. Using an Ogston obstruction model, we show that the electrophoretic mobility is not affected by the presence of curved field lines. In other words, the Nernst-Einstein relation between the mobility and the diffusion coefficient is valid regardless of the electrical properties of the gel fibers. Although this finding may greatly simplify the development of ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Over the last decade, our group [47,72,[149][150][151][152][153][154] has developed a numerically exact calculation technique for the mobility m and the diffusion coefficient D (which are essentially the same in the zero field limit, see Section 14) of small analytes evolving on a lattice in the presence of immobile obstacles. In a recent paper [72], we presented an extension of our model that used the BFM to treat the case of macromolecules.…”
Section: Modeling Gel Electrophoresis With Reptonsmentioning
confidence: 96%
See 3 more Smart Citations
“…Over the last decade, our group [47,72,[149][150][151][152][153][154] has developed a numerically exact calculation technique for the mobility m and the diffusion coefficient D (which are essentially the same in the zero field limit, see Section 14) of small analytes evolving on a lattice in the presence of immobile obstacles. In a recent paper [72], we presented an extension of our model that used the BFM to treat the case of macromolecules.…”
Section: Modeling Gel Electrophoresis With Reptonsmentioning
confidence: 96%
“…The fact that separation does occur experimentally can be attributed to various factors (such as partly conducting obstacles or the deformation of the macromolecules), but this example illustrates that a realistic representation of the field lines can become crucial in the interpretation of experimental results. On the other hand, the curvature of the field lines around obstacles does not always affect the dynamics; indeed, our group has shown that in general, in the zero-field limit, the electrophoretic mobility and the diffusion coefficient of a point-particle is independent of both the field lines curvature and the obstacle shape [47].…”
Section: Ratchetsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a number of phenomena missing in the ORMC model, such as the role of gel disorder, percolating pathways and dead-ends. Slater and co-workers [91][92][93][94][95][96][97][98][99][100] have called into question the fundamental validity of the ORMC model for describing gel electrophoresis in the limit R g < b.…”
Section: Introductionmentioning
confidence: 99%